Efficient production of functional cholera toxin B subunit using geminiviral replicons in Nicotiana benthamiana - Kim, Nan-Sun; Lee, Jihyea; Lee, Juho; Lee, Seon-Kyeong; Lee, Kyeong-Ryeol (Frontiers in Bioengineering and Biotechnology, 2025)
The cholera toxin B subunit (CTB) has the potential to be a carrier molecule and an effective adjuvant for mucosal vaccines because of its ability to enhance immune responses to antigens. CTB proteins have been expressed in plant-based expression systems. In this study, we used geminiviral replicon systems to transiently express CTB in Nicotiana benthamiana. We developed a high-level expression system that uses combinations of the replication machinery of geminivirus, including tomato yellow leaf curl virus (TYLCV), honeysuckle yellow vein virus (HYVV), and beet mild curly top virus (BMCTV). These were named TIR + TC123, HIR + HC123, and BIR + BC1, respectively. The plant-optimized CTB gene was cloned into each geminivirus IR-carrying vector and co-infiltrated into N. benthamiana leaves. Immunoblot analysis verified the synthesis and assembly of CTB into pentamers. The highest CTB protein level, approximately 2.5 mg/g fresh weight (22% of total soluble protein), was observed on day 5 in the BMCTV combination in N. benthamiana. CTB transiently expressed in plants using geminivirus-based viral vector systems demonstrated enhanced protein expression levels and a strong affinity for GM1-ganglioside. This suggests that the CTB subunits form an active pentamer, implying its potential as an adjuvant for mucosal vaccines.